Allogeneic haematopoietic cell transplantation impacts on outcomes of mantle cell lymphoma with TP53 alterations. (11th December 2018) - Lin, Richard J.; Ho, Caleb; Hilden, Patrick D.; Barker, Juliet N.; Giralt, Sergio A.; Hamlin, Paul A.; Jakubowski, Ann A.; Castro‐Malaspina, Hugo R.; Robinson, Kevin S.; Papadopoulos, Esperanza B.; Perales, Miguel‐Angel; Sauter, Craig S.
Summary: TP53 alterations portend extremely poor prognosis in patients with mantle cell lymphoma treated with standard treatment modalities. We reviewed outcomes of 42 patients with available TP53 status who had received a reduced‐intensity or non‐myeloablative allogeneic haematopoietic cell transplant at our institution. We demonstrated a 2‐year overall survival and progression‐free survival of 78% [95% confidence interval (CI) 60–88] and 61% (95% CI 43–75), respectively. The 2‐year cumulative incidences of relapse and non‐relapse mortality were 19% and 20%, respectively. Importantly, there is no significant difference among patients with and without TP53 alterations, suggesting for the first time a beneficial treatment modality for these high‐risk patients.